A Hybrid Column Generation and Clustering Approach to the School Bus Routing Problem with Time Windows - Lopez Santana, Eduyn Ramiro; Romero Carvajal, Jose de Jesus (Ingeniería, 2015)
This paper attempts to solve the School Bus Routing Problem with Time Windows that consists of finding the best set of routes to pick up students distributed geographically with constraints as capacity, time windows and maximum travel time. We formulated the problem as a classic Vehicle Routing Problem with Time Windows and solved it using an approach based on a clustering algorithm and column generation method. A real world case from a school in Bogota, Colombia is presented including 600 students to pick up ´ in near 400 nodes located in urban and rural areas. The obtained results demonstrate a reduction as the problem’s complexity and an improvement on the performance measures of the proposed method.